Illustrated Neuropathologic Diagnosis of Alzheimer’s Disease - Nicholas Doher; Vahid Davoudi; Shino Magaki; Ryan A. Townley; Mohammad Haeri; Harry V. Vinters (Neurology International, 2023)
As of 2022, the prevalence of Alzheimer’s disease (AD) among individuals aged 65 and older is estimated to be 6.2 million in the United States. This figure is predicted to grow to 13.8 million by 2060. An accurate assessment of neuropathologic changes represents a critical step in understanding the underlying mechanisms in AD. The current method for assessing postmortem Alzheimer’s disease neuropathologic change follows version 11 of the National Alzheimer’s Coordinating Center (NACC) coding guidebook. Ambiguity regarding steps in the ABC scoring method can lead to increased time or inaccuracy in staging AD. We present a concise overview of how this postmortem diagnosis is made and relate it to the evolving understanding of antemortem AD biomarkers.